ARCA PERWUJUDAN PENDETA DI PURA CANDI AGUNG DESA LEBIH, KABUPATEN GIANYAR - Pradnyana, I Gde Putu Surya (Humanis, 2016)
Archaeological study seeks to uncover the history of past human cultures through the objects left behind. The heritage objects basically have a very high historical value. Besides these objects also have informational value, artistic value and the value religion. Objects is a reflection of ideas, activities, and a manifestation of a human civilization. The habit of making statues embodiment can be regarded as an element of sustainability culture that has been known since pre Hindu. In relation to the embodiment statue temple priest contained in Candi Agung Village Lebih, Gianyar, an embodiment of a prominent statue of Shiva followers, it is not separated from the conception of the worship of ancestral spirits and functioned as pelidung village of distress that attack. This statue by society devotees, used as media of religious meditation, as well as complementary ritual believed to provide protection and welfare.
Keywords: Embodiment statue, conception, function, periodization, Candi Agung Temple